2018
DOI: 10.1128/msphere.00558-18
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Escherichia coli Diversity in the Gastrointestinal Tracts of Tanzanian Children with and without Exposure to Antibiotics

Abstract: This study increases the number of resident Escherichia coli genome sequences, and explores E. coli diversity through longitudinal sampling. We investigate the genomes of E. coli isolated from human gastrointestinal tracts as part of an antibiotic treatment program among rural Tanzanian children. Phylogenomics demonstrates that resident E. coli are diverse, even within a single host. Though the E. coli isolates of the gastrointestinal community tend to be phylogenomically similar at a given time, they differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 66 publications
7
28
1
Order By: Relevance
“…1). The high diversity observed among these Bangladeshi E. coli isolates is in line with recent studies in other rural or semirural communities in LMICs (23,34). For instance, Richter et al found high interindividual diversity among gastrointestinal E. coli isolates in Tanzanian children and high intraindividual temporal diversity in samples from the same child during a 6-month period (34).…”
Section: Discussionsupporting
confidence: 83%
“…1). The high diversity observed among these Bangladeshi E. coli isolates is in line with recent studies in other rural or semirural communities in LMICs (23,34). For instance, Richter et al found high interindividual diversity among gastrointestinal E. coli isolates in Tanzanian children and high intraindividual temporal diversity in samples from the same child during a 6-month period (34).…”
Section: Discussionsupporting
confidence: 83%
“…However, in a recent analysis of E. coli strains isolated from healthy individuals who traveled from the United Kingdom to South Asia (Bevan et al 2018), not only phylogroups B2 and D strains but also phylogroup A strains were predominant. In another recent study that analyzed E. coli isolates from Tanzanian children under the age of 5, phylogroups A and B1 strains were most frequently isolated (Richter et al 2018). Although 56 of the 168 phylogroup A strains in our data set were human commensal isolates (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…We performed a detailed characterization of LREC pipolin positive strains, both by 153 conventional methods and whole-genome sequence (WGS) analysis ( Table 2 and 154 Table S1). We found that pipolins were present in phylogroup A (11 new strains and 155 the reference isolate 3-373-03-S1-C2 [13]), but also in B1 (3 strains) and C (6 strains).…”
mentioning
confidence: 80%
“…Obtained sequences are available as a NCBI Bioproject PRJNA610160 (see Table S1 for Biosamples Ids and Enterobase Uberstrain codes for each strain). Strain 3-373-03_S2_C2 [13] was sequenced and analyzed in parallel as a reference, but it was not included in the BioProject to avoid redundancy.…”
Section: Conventional Typing Of Lrec Pipolin-harboring Strainsmentioning
confidence: 99%